Peran Komunikasi Verbal dan Nonverbal dalam Hubungan Manusia - Alqanitah Pohan (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2015)
Verbal communication (verbal communication) is a form of communication communicator to the communicant with the written way (written) or verbal (oral). Verbal communication occupies a large portion. Because in reality, ideas, thoughts or decisions, more easily conveyed verbally than non-verbal. With hope, the communicant (good listener maun reader) can more easily understand the messages being delivered. example: verbal communication through speech can be done by using the media, an example of someone who chatted by phone. While verbal communication through writing done indirectly between communicators with the communicant. Information process is done by using media such as letters, paintings, drawings, graphics and others. Non-verbal communication (nonverbal communicarion) occupies an important portion. Many verbal communication is not effective simply because komunikatornya not use non-verbal communication with both at the same time. Through non-verbal communication, people can take a conclusion about a conclusion about the various persaan people, pleasure, hate, love, miss and various other emotions. Relation to the business world, non-verbal communication can help communicators to further reinforce the message delivered at the same time understand the communicant reaction when receiving a message. Forms of non-verbal communication alone among them is, gestures, facial expressions, password, symbols, clothing sergam, color and tone of voice.